Extinção do direito à repetição do indébito tributário e à compensação = Extinction of the right of tax overpayments and to the compensation - Machado, Hugo de Brito (2018)
Submitted by Eliana null (leila@stj.jus.br) on 2018-05-16T13:01:48Z No. of bitstreams: 2 extincao_direito_repeticao_machado.pdf: 195767 bytes, checksum: 04778ea5ea4d6978a327cbe2870a4168 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)